Pemenuhan Kewajiban Negara Terhadap Pekerja Terdampak Kebijakan Penanganan Covid-19 Di Kota Semarang - Rahayu Rahayu; Diastama Anggita Ramadhan; Pulung Widhi Hari Hananto (Jurnal Hukum IUS QUIA IUSTUM, 2021)
The employment sector is the most severely affected by the Covid-19 pandemic, including in Indonesia. More than 2 million people have lost their jobs, meaning they no longer have the income to make ends meet. This study aims to identify and analyze the impact of the Covid-19 pandemic on the employment status of workers in Semarang City, as well as the efforts made by the Semarang City Government to carry out its obligations to fulfill the rights of these workers. This research is a qualitative research with a doctrinal approach, and uses secondary data obtained through literature study in the form of regulatory and policy instruments as well as relevant scientific concepts. This study concludes that the Covid-19 pandemic has an impact on the employment status of some workers in the city of Semarang, namely experiencing termination of employment (PHK) or being ‘sent home'. Regarding this situation, the Semarang City Government is trying its best so that the rights of workers affected by the Covid-19 handling policy can be fulfilled by the company by encouraging an agreement to be reached between the parties. For workers who are affected, the Semarang City Government also provides various stimuli and social assistance.